Implementasi Metode Agile Development Pada Aplikasi Custom Sistem Stok Card Berbasis Website (Studi Kasus: Pt. Rosso Bianco) - Galuh Saputri; Ikhsannudin Ma'sum (Institut Sains dan Teknologi Nasional, 2022)
Abstract System inventory goods is a system that explains how the transaction of receiving goods and transactions.the use of goods which contains the status of the stock of goods can help increase productivity.companies. PT. Rosso Bianco always keeps records of inventory. for inventory data processing, inventory of goods is still recorded using paper media by the admin (user). For inventory data collection, it is only recorded in the general ledger, so that problems often occur when errors occur in the calculation of goods produced which are inaccurate and inefficient and errors often occur. In addition, the storage is still using Microsoft Excel, so the process of recording causes processing of goods data to take a long time. And every time there is a report on the sale of goods, it requires a long time to process, so that reports are often delayed. This system uses the PHP Native programming language and uses the MySql Database because it is more accessible to users. Keywords: Inventory of goods, Inventory, Stock of Goods